Analisis Faktor–Faktor yang Mempengaruhi Alokasi Anggaran Belanja Modal - Agus Sukarno; Hadioetomo Hadioetomo; Agus Haryadi (Prodi Akuntansi - FEB Universitas Muhammadiyah Gresik, 2019)
Regional Autonomy intended that each region can be independent in conducting regional development in the form of capital cost in order to increase the area of fixed assets. The purpose of this study is to determine whether there is the influence of the Economic Growth, General Allocation Fund, Special Allocation Fund, Revenue Sharing Fund, Original Income Area, SiLPA, and Total Area against Capital Expenditure of the District/City in Indonesia. This study used secondary data obtained from the Supreme Audit Agency in 2017. The sample used in the study were 180 District/City located in Indonesia. The way to analyze the data by using multiple linier regression analysis. Based on the analysis stated that the variable Revenue Sharing Fund, Original Income Area, Total Area effect on Capital Expenditure. While Economic Growth, General Allocation Fund, Special Allocation Fund, SiLPA does not effect on Captital Expenditure.